Crystal Structure and Properties of Na2O-Modified K0.47Na0.47Li0.06Nb0.96Sb0.04O3-SrTiO3 Piezoelectric Ceramics - Yin, Qiyi; Sun, Zhaoqi; Tian, Changan; Jiang, Xishun; Chen, Jihai; Xie, Jinsong; Bao, Meiling (Asian Journal of Chemistry, 2013)
Na2O-modified (1-x)K0.47Na0.47Li0.06Nb0.96Sb0.04O3-xSrTiO3 (abbreviated as KNLNS-ST, x = 0, 0.015, 0.035, 0.055, 0.08) Lead-free piezoelectric ceramics were fabricated by conventional ceramics sintering technique at 1050 ºC and their crystal structure, dielectric and piezoelectric properties were systematically investigated. The X-ray diffraction revealed that all ceramics possessed a pure perovskite structure and a morphotropic phase boundary between the tetragonal and rhombohedral phases was identified in the composition range of 0.015 £ x £ 0.035, leading to a significant improvement in the electrical properties of the ceramics. The ceramic with x = 0.035 exhibited excellent properties at room temperature (d33=186pC/N, kp = 42 %, er = 1116, tan d = 1.8 %) owning to the formation of morphotropic phase boundary. These results indicated that the ceramic is a promising candidate material for lead-free piezoelectric ceramics.